Chemical composition and anti-cholesterol activity of tea (Camellia sinensis) flowers from albino cultivars - Gao, Ying; Han, Zhen; Xu, Yong-Quan; Yin, Jun-Feng (Frontiers in Nutrition, 2023)
Albino tea cultivars are mutant tea plants with altered metabolisms. Current studies focus on the leaves while little is known about the flowers. To evaluate tea flowers from different albino cultivars, the chemical composition and anti-cholesterol activity of tea flowers from three albino cultivars (i.e., Baiye No.1, Huangjinya, and Yujinxiang) were compared. According to the results, tea flowers from Yujinxiang had more amino acids but less polyphenols than tea flowers from the other two albino cultivars. A reduced content of procyanidins and a high chakasaponins/floratheasaponins ratio were characteristics of tea flowers from Yujinxiang. In vitro anti-cholesterol activity assays revealed that tea flowers from Yujinxiang exhibited stronger activity in decreasing the micellar cholesterol solubility, but not in cholesterol esterase inhibition and bile salt binding. It was noteworthy that there were no specific differences on the chemical composition and anti-cholesterol activity between tea flowers from albino cultivars and from Jiukeng (a non-albino cultivar). These results increase our knowledges on tea flowers from different albino cultivars and help food manufacturers in the cultivar selection of tea flowers for use.